Distribution of HLA-A, -B, and -C Alleles and HLA/KIR Combinations in Han Population in China. (5th June 2014) - Shen, Yunsong; Cao, Danfeng; Li, Yalin; Kulski, J. K.; Shi, Lei; Jiang, Hongjun; Ma, Qianli; Yu, Jiankun; Zhou, Jingxian; Yao, Yufeng; Shi, Li
Abstract : We investigated polymorphisms of the human leukocyte antigen (HLA) class I (A, B, and C) loci of a Han population ( n, 239) from the Yunnan province, Southwest China, using high-resolution polymerase chain reaction-Luminex (PCR-Luminex) typing. We combined the HLA data from this study with the KIR genotypes from a previous study of this Han population to analyze the combination of KIR/HLA ligands. A total of 27 HLA-A, 54 HLA-B, and 31 HLA-C alleles were found in this population. The frequencies of A * 11:01, A * 24:02, B * 40:01, B * 46:01, C * 01:02, C * 03:04, and C * 07:02 were all > 10%. The following haplotypes were common, with frequencies > 5%: 1 A-B (A * 02:07-B * 46:01), 2 A-C (A * 02:07-C * 01:02, and A * 11:01-C * 07:02), 4 C-B (B * 13:01-C * 03:04, B * 40:01-C * 07:02, B * 46:01-C * 01:02 and B * 58:01-C * 03:02), and 1 A-C-B (A * 02:07-C * 01:02-B * 46:01). Analysis of KIR3D and their ligands HLA-A3/A11 and HLA-Bw4 showed that the frequencies of 3DL2 + -A3/A11 + and 3DL2 + -A3/A11 − were 0.527 and 0.473, and the frequencies of 3DL1 + -Bw4 +, 3DL1 + -Bw4 −, 3DL1 − -Bw4 +, and 3DL1 − -Bw4 − were 0.552, 0.397, 0.038, and 0.013, respectively. The results of KIR/HLA-C combination analysis showed that all individuals had at least one inhibitory or activating KIR/HLA-C pair, and one KIR/HLA-C pair was the most frequent (157/239), followed by two pairs (46/239), three pairs (33/239), and no pairs (3/239). Comparison of KIR gene and HLA gene and their pair frequency between Yunnan Han and the isolated Han (FYDH) who also lived in Yunnan province showed no significant difference (P > 0.05 ) in KIR frequencies, but significant differences (P < 0.05 ) for some HLA allele frequencies. In addition, there was no significant difference (P > 0.05 ) between the two populations for KIR/HLA pairs.